Microbial load in tannery and textile effluents and their receiving rivers of Dhaka - Das, Monika; Ahmed, Md Kawser; Begum, Fauzia; Parveen, Sahana; Islam, Md Monirul; Begum, Mahmuda (Dhaka University Journal of Biological Sciences, 2011)
The present study was undertaken to investigate the occurrence of some selected microorganisms in industrial effluents and in the river Buriganga and Karnatoli, which receive the industrial effluents directly from industries, with a view to evaluate the effect of industrial effluents on river. The total viable bacterial count (TVBC) in both tannery and textile effluents were slightly higher in dry season than those of rainy and summer. The TVBC in Buriganga River ranged from 3.4 × 105 to 9.6 × 105, 2.2 × 104 to 1.2 × 105 and 7.2 × 104 to 4.5 × 105 cfu/ml in dry, rainy and summer seasons, respectively, and the TVBC in Karnatoli River ranged from 4.9 × 105 to 5.4 ×106, 1.2 × 105 to 1.0 × 105 and 5.3 × 104 to 3.8 × 105 cfu/ml in dry, rainy and summer seasons, respectively. Pseudomonas spp. in effluents and river water were also slightly higher in dry season than that of rainy and summer seasons due to increase in water level. The total coliform and fecal coliform counts of the industrial effluents and discharge point in the river were always very high, which was >2.4 × 103cfu/100 ml in all seasons as measured by the MPN method. Salmonella, Vibrio and Staphylococcus were frequently isolated from all the sampling points throughout the year with a few exceptions. This study indicates that the water of the river Buriganga and Karnatoli is heavily contaminated with both industrial wastes and domestic sewage materials. The bacteriological state of the water of the rivers is comparable to that of the effluents. The presence of pathogenic organisms may pose health hazards to the users of the river water and also poses risks for the aquatic organisms especially fish of the water bodies. Key words: Microbial load; Tannery; Textile effluents; Receiving rivers DOI: http://dx.doi.org/10.3329/dujbs.v19i1.8946 DUJBS 2010; 19(1): 73-81